2000
DOI: 10.1080/10889860091114293
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Aerobic Trichloroethene Attenuation Using First-Order Rate Estimation

Abstract: Natural attenuation of trichloroethene (TCE) was evaluated for a groundwater plume at the Idaho National Engineering and Environmental Laboratory. Significant evidence demonstrated that reductive dechlorination is occurring, but is limited to a small area around the contamination source. In spite of this, the plume is relatively stable. Three first-order rate estimation methods were used to help understand transport processes affecting TCE in the large, aerobic portion of the plume. Two of the methods gave att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
6
25
0
Order By: Relevance
“…Though the extent of this plume is quite large, it does not appear to be migrating farther from the initial point of contamination. A previous study ruled out abiotic loss as the only reason for this observed attenuation (47). In addition, direct evidence that TCE cometabolism is occurring at the TAN site within the plume of TCE contamination has been reported (M. H. Howard-Jones, W. K. Keener, R. A. Wymore, F. S. Colwell, K. S. Sorenson, and M. E. Watwood, Abstr.…”
mentioning
confidence: 98%
“…Though the extent of this plume is quite large, it does not appear to be migrating farther from the initial point of contamination. A previous study ruled out abiotic loss as the only reason for this observed attenuation (47). In addition, direct evidence that TCE cometabolism is occurring at the TAN site within the plume of TCE contamination has been reported (M. H. Howard-Jones, W. K. Keener, R. A. Wymore, F. S. Colwell, K. S. Sorenson, and M. E. Watwood, Abstr.…”
mentioning
confidence: 98%
“…The aquifer resides deep within fractured basalt, making contaminant characterization and ex situ remediation difficult and expensive. TCE concentrations of at least 32,000 g liter Ϫ1 have been measured within the plume that spans an area of approximately 1 by 3 km and extends from 64 m to greater than 155 m in depth (74).…”
mentioning
confidence: 99%
“…Though the extent of this plume is quite large, it does not appear to be migrating farther from the initial point of contamination. A previous study ruled out abiotic loss as the only reason for this observed attenuation (47). In addition, direct evidence that TCE come- Previously, methanotrophs, propanotrophs, nitrifiers, and phenol oxidizers have been isolated from groundwater within the TAN site (7).…”
Section: Discussion 315mentioning
confidence: 99%